Pemikiran Kuki Shuzo Mengenai Konsep Iki dan Relevansinya Pada Estetika Modern - Yutaro Yoshikoshi; Bartolomeus Samho (Universitas Katolik Parahyangan, 2024)
This article intends to explore the concept of iki aesthetics and investigate its relevance to modern aesthetics. The method used in this article is qualitative, a literature study that specifically focuses on using the thoughts of the philosopher Kuki Shuzo in the book The Structure of Iki. The results show that iki consists of bitai, ikiji, and akirame and that iki is also still relevant for modern aesthetics. In conclusion, iki evokes a certain kind of sensibility through the tension that emerges through dualistic relationships. And this unique form of sensibility proves to still be very relevant in modern aesthetics. This is proven by the fact that Japanese aesthetics are also in demand by people outside of Japan and that there are still various inquiries into modern aesthetics whilst takin into account the role of iki.